Impulse Buying Intentions of Gen Z’s Consumers From Hedonic Shopping Perspective for Apparels - Agrawal, Surabhi; Pandey, Akhilesh Chandra (Apex Journal of Business and Management, 2024)
The purpose of the study is to explain the paths that lead to impulse buying intentions of Gen Z’s consumer behaviour for apparels by hedonic shopping perspective. Data were collected using a structured questionnaire from a sample of 257 consumers from north India aged 15 to 27 by using the simple random sampling. For testing the research hypotheses, regression analysis was employed using SPSS. The result of the study reveals that all the five variables i.e novelty, praise from others, fun, escapism, social interaction of hedonic shopping value is positive associated with Impulsive buying intentions of Gen Z’s for apparels. The behaviour of eastern Uttar Pradesh consumers would be informative for consumer behaviour researchers, retailers and marketers. The study neglects the demographic and socio-psychological factors which are the major factor that affects consumer’s purchase behavior. This research adds to the understanding of association between hedonic shopping and impulse purchase. In this regard, the findings of the study would make a contribution to scant empirical works of impulse buying behaviour of apparel purchasers which may help marketers to give insight to newer dimensions and improve their business strategy.